Nonalcoholic Fatty Liver Disease for Identification of Preclinical Carotid Atherosclerosis. Issue 3 (January 2016) - Sinn, Dong Hyun; Cho, Soo Jin; Gwak, Geum-Youn; Cho, Juhee; Gu, Seonhye; Seong, Donghyeong; Kang, Danbee; Kim, Hyunkyoung; Yi, Byoung-Kee; Paik, Seung Woon
Abstract : Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with cardiovascular disease, yet whether identification of NAFLD in asymptomatic individuals is helpful over established risk factors remains unknown. A total of 37, 799 asymptomatic adults aged 20 years or older who underwent comprehensive health check-up examination, including abdominal and carotid artery duplex ultrasonography (US) were included in the analysis. Nonalcoholic fatty liver disease was diagnosed with US and exclusion of secondary causes of fat accumulation or other causes of chronic liver disease, and graded as mild or moderate to severe fatty liver. Individuals with carotid plaque identified on carotid artery US were considered at risk for cardiovascular disease. Metabolic syndrome (MetS) was defined by the adult treatment panel III criteria. Nonalcoholic fatty liver disease was an independent factor associated with carotid plaque in a dose-dependent manner (odds ratio [OR]; 95% confidence interval [CI]: 1.09 [1.03–1.16] and 1.13 [1.06–1.21] for mild and ≥ moderate degree of NAFLD). Among clinically-relevant subgroups, NAFLD was more closely associated with carotid plaque in young adults (aged < 60 years) without MetS (OR [95% CI]: 1.13 [1.03–1.19] and 1.16 [1.06–1.27] for mild and ≥ moderate degree of NAFLD) than old adults (aged ≥ 60 years) or with MetS (OR [95% CI]: 1.06 [0.97–1.17] and 1.07 [0.97–1.19] for mild and ≥ moderate degree NAFLD). In young adults without MetS, the prevalence of carotid plaques was 32.8% and the sensitivity and specificity of NAFLD for carotid plaque was 0.38 and 0.67, respectively. In conclusion, NAFLD is associated with carotid plaque independent of traditional risk factors, especially in young adults without MetS. Nonalcoholic fatty liver disease could help identify additional individuals with preclinical atherosclerosis in asymptomatic young adults without MetS, yet, showed suboptimal performance as a screening tool.